The acute effect of various doses of caffeine on power output and velocity during the bench press exercise among athletes habitually using caffeine - Wilk, M.; Filip, A.; Krzysztofik, M.; Maszczyk, A.; Zajac, A. (Nutrients, 2019)
Background: Previously studies confirm ergogenic effects of caffeine (CAF); however there is no available scientific data regarding the influence of acute CAF intake on power output in athletes habitually consuming CAF. The main goal of this study was to assess the acute effect of 3, 6, 9 mg/kg/b.m. doses of CAF intake on power output and bench press bar velocity in athletes habitually consuming CAF. Methods: The study included 15 healthy strength-trained male athletes (age = 26.8 ± 6.2 years, body mass = 82.6 ± 9.7 kg; BMI = 24.8 ± 2.7; bench press 1RM = 122.3 ± 24.5 kg). All participants were habitual caffeine consumers (5.2 ± 1.2 mg/kg/b.m.; 426 ± 102 mg of caffeine per day). This study had a randomized, crossover, double-blind study design where each participant performed four different experimental sessions, with one week interval between each trial. In every experimental session participants performed bench press, three sets of five repetitions at 50% 1RM. The power output and bar velocity assessments under four different conditions: a placebo (PLAC), and three doses of caffeine ingestion: 3 mg/kg/b.m. (CAF-3), 6 mg/kg/b.m. (CAF-6) and 9 mg/kg/b.m. (CAF-9). Results: The statistical significance was set at p < 0.05. The repeated measures ANOVA between PLAC and CAF-3; CAF-6; CAF-9 revealed no statistically significant differences in power output and velocity of the bar during the bench press exercise. A large effect size (ES) in mean power-output was found between PLAC and CAF-9 in Sets 1 and 2. A large ES in peak power-output was found between PLAC and CAF-6 in Set 2, and between PLAC and CAF-9 in Sets 1 and 2. A large ES in peak velocity was found between PLAC and CAF-9 in Sets 1-3. Conclusion: The results of the present study indicate that acute doses of CAF before exercise does not have a significant effect on power output and bar velocity in a group of habitual caffeine users.